Immodest Greatness of the Heart: An Introduction to the Anti-Theory of Culture of St. Francis of Assisi - Kubicki, Roman (Sensus Historiae, 2024)
The present paper discusses the system of values that St. Francis of Assisi followed throughout his life. The major source of inspiration is provided by the book by the Polish writer Zofia Kossak, “Blessed Are the Meek,” which is treated it as an important biography of Francis and a vivid picture of his age. The life of Francis shows him to have resembled the Nietzschean superhuman in daring to reject the accepted norms and rules of his time.